V‐model with fuzzy quality function deployments for mobile application development. Issue 1 (19th October 2022) - Lim, Chong Hon; Chin, Jeng Feng
Abstract: Mobile application (app) development is a subset of software development distinguished by a short development life cycle, rapidly changing business requirements, mobile device technical specifications, and operating system compatibility. The study presents a V‐model mobile app development technique that combines two fuzzy quality function deployment (FQFD) phases. In mobile app development, user requirements are often misunderstood, resulting in poor mobile app design. The research motivation for employing FQFD is to obtain more accurate deductions of human (user or design team) inputs affected by intrinsic vagueness and ambiguity in linguistics. The combination hence delivers synergistic benefits, where FQFDs more effectively solicits and breaks down the voice of the customer (VOC) and system requirements, and the V‐model aligns the development to the broken‐down requirements. The development of an online statistical process control app was demonstrated. FQFD structurally related user requirements, system requirements, and design strategies in the V‐model's verification phases. The validation phases used test plans created during the verification phases to detect and correct programming errors. In the final validation stage, the focus group agreed that the mobile app met all of the user requirements. This study adds to the methodology's novelty by proposing and demonstrating the integration of the FQFD and V‐model into the development of mobile apps. As a result of the limitation, other areas of software engineering, such as time and resource coordination and release management, are not considered. Abstract : The paper proposes V‐model mobile app development technique that combines two fuzzy quality function deployment (FQFD) phases. The development of an online statistical process control app was demonstrated. FQFD structurally related user requirements, system requirements, and design strategies in the V‐model's verification phases. The validation phases used test plans created during the verification phases to detect and correct programming errors. In the final validation stage, the focus group agreed that the mobile app met all of the user requirements.